Dietary breadth and ecological plasticity facilitate invasion potential in a large omnivorous lizard - Harman, Madison E. A.; Fuller, Nicole R.; Baiser, Benjamin; Blackburn, Jason K.; Li, Xiaolong; Currylow, Andrea F.; Yackel Adams, Amy A.; Falk, Bryan G.; Romagosa, Christina M. (Frontiers in Amphibian and Reptile Science, 2025)
Invasive species are a widely recognized threat to ecosystems, where they can negatively affect native species through mechanisms such as predation, competition, and ecosystem modification, including altering seed dispersal. Quantifying these effects is essential to properly assess risk and inform management efforts. In Florida, USA, where introductions are numerous and frequent, one prominent invasive species is the Argentine black and white tegu (Salvator merianae). This large omnivorous lizard likely contributes to ecosystem disruption through all three mechanisms. To better understand the role of invasive tegus in Florida ecosystems, we analyzed the diet of two disjunct tegu populations: Miami-Dade County (established in approximately 2011) and Charlotte County (established in 2018). We identified gastrointestinal contents from 275 tegus caught between 2016 and 2021. Diet items spanned a vast range of vertebrates, invertebrates, and plants, representing 12 classes, 63 orders, and 126 families across a mix of native, invasive, and agricultural species. The most common diet groups were insects (in 97% of diets), mammals (81%), fruit (77%), and snails (60%). Vertebrate consumption was substantially more frequent in the invasive Florida populations relative to tegus in their native range. Tegus also demonstrated a tolerance for “toxic” plant and wildlife species. We used distance-based redundancy analyses to examine the influence of size, sex, capture month, habitat, and spatial autocorrelation on diet composition within each population. In both Florida populations, larger tegus and individuals captured earlier in the year tended to have more diverse diets, including higher frequencies of invasive gastropods and various vertebrates. Smaller tegus and those caught in later months exhibited lower dietary diversity and a greater reliance on fruits and insect groups, such as orthopterans. Our findings corroborate the generalist nature of tegus, whose broad and opportunistic diets likely expose a wide range of native species to predation and may facilitate the dispersal of invasive plants. Tegus’ ability to forage in both natural and degraded habitats likely increases the difficulty of extirpation and therefore supports the need for swift removal efforts in response to new introductions.